Upacara Ritual Rukun Kematian Agama Hindu Kaharingan Suku Dayak Dusun di Kecamatan Dusun Selatan di Kabupaten Barito Selatan - Sulandra Sulandra (Tampung Penyang, 2025)
For adherents of the Kaharingan Hindu religion, the death ritual is a tradition and a religious ritual that must be carried out, thus becoming a belief/faith as one of the rituals of the Kaharingan Hindu religion. The implementation of the Kaharingan Hindu death ritual of the Dusun Dayak Tribe includes the initial process of death, which is carried out by tuntung or nuntung. Next, oseng annoi, which involves handling the body and bathing the body. Next, pangumma' panguyang, which involves the removal of clothing and other necessary items from the deceased, which are usually accompanied by the deceased. Afterward, a coffin (rarung) is constructed, the body is placed in the coffin, and the burial ceremony follows the death ritual of the Dusun Dayak Tribe in Dusun Selatan District, South Barito Regency.